3D Analysis of the Proximal Interphalangeal Joint Kinematics during Flexion. (5th November 2013) - Hess, Florian; Fürnstahl, Philipp; Gallo, Luigi-Maria; Schweizer, Andreas
Abstract : Background . Dynamic joint motion recording combined with CT-based 3D bone and joint surface data is accepted as a helpful and precise tool to analyse joint. The purpose of this study is to demonstrate the feasibility of these techniques for quantitative motion analysis of the interphalangeal joint in 3D. Materials and Method . High resolution motion data was combined with an accurate 3D model of a cadaveric index finger. Three light-emitting diodes (LEDs) were used to record dynamic data, and a CT scan of the finger was done for 3D joint surface geometry. The data allowed performing quantitative evaluations such as finite helical axis (FHA) analysis, coordinate system optimization, and measurement of the joint distances in 3D. Results . The FHA varies by 4 . 9 ± 1.7 ° on average. On average, the rotation in adduction/abduction and internal/external rotation were 0 . 3 ± 0.91 ° and 0 . 1 ± 0.97 °, respectively. During flexion, a translational motion between 0.06 mm and 0.73 mm was observed. Conclusions . The proposed technique and methods appear to be feasible for the accurate assessment and evaluation of the PIP joint motion in 3D. The presented method may help to gain additional insights for the design of prosthetic implants, rehabilitation, and new orthotic devices.